L’iconographie de l’Indien dans le cinéma américain : de la manipulation de l’image à sa reconquête - Anne Garrait-Bourrier (Revue LISA)
The Native American ethnic group has always been used and abused, not to say manipulated, by the medium of cinema. Such an exploitation of the image of the Indian responded to the demands of a new form of artistic expression which was extremely graphic and violent, as were graphic and visually violent the first western movies. As an artistic genre, cinema really manipulated the classical stereotypes related to the Indian in order to use him as a « character » detached from any historical reality. It is not surprising though to see that the evolution over time of this widely exploited « character » can be equated to a long wandering from exaggeration to understatement, to eventually reach the political expression of the Indians themselves. All this turmoil and agitation did correspond to the modus operandi of the Hollywoodian « system ».